2008
DOI: 10.1038/ijir.2008.61
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a genetic etiology to ejaculatory dysfunction

Abstract: A number of theoretical approaches to understanding the etiology of ejaculatory dysfunction have been proposed, but no study has yet found conclusive evidence that premature (PE) or delayed (DE) ejaculation is under genetic control. We conducted twin model fitting analyses on different indicator variables of ejaculatory function on a population-based sample of 3946 twins and their siblings (age 18-48; mean ¼ 29.9 years) to investigate genetic, shared environmental and unique environmental effects on PE and DE.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
55
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 24 publications
(32 reference statements)
8
55
0
1
Order By: Relevance
“…A genetic etiology of PE in humans was previously suggested in 1940 [13] when Schapiro noted that PE seems to be familial. This conclusion has been supported in more recent publications by Jern et al [7] and Waldinger et al [14] . With selective 5-HT reuptake inhibitors successfully used in the treatment of PE, many scientists have focused their interest on 5-HT metabolization and its receptors.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…A genetic etiology of PE in humans was previously suggested in 1940 [13] when Schapiro noted that PE seems to be familial. This conclusion has been supported in more recent publications by Jern et al [7] and Waldinger et al [14] . With selective 5-HT reuptake inhibitors successfully used in the treatment of PE, many scientists have focused their interest on 5-HT metabolization and its receptors.…”
Section: Discussionsupporting
confidence: 76%
“…Waldinger and colleagues [4][5][6] postulated LPE as a neurobiological dysfunction with a genetic vulnerability for short IELT related to decreased central 5-HT neurotransmission and/or 5-HT receptor dysfunction (i.e., hypofunction of the 5-HT 2C and/or 5-HT 1B receptors or hyperfunction of the 5-HT 1A receptor). Jern et al [7] conducted an investigation of 3,946 twins and their siblings that indicated a significant moderate genetic effect for PE.…”
Section: Introductionmentioning
confidence: 99%
“…The results of 21 responders were compared against 63 age matched controls from a population based sample of male twins and their brothers. 9 In the IIEF questionnaire scores over 25 indicate normal erectile function and scores 22-25 indicate mild dysfunction. 10 In this study erectile function was considered satisfactory if IIEF score was 22 or more.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Participants who had not engaged in partnered sexual activity during this time were excluded from further statistical analyses. The indicator variables were subjected to factor analyses to determine their reliability (see [ 5,11 ] for a more detailed description of this procedure). Factor analyses conducted on these indicator variables [ 11 ] have shown good factorability (Kaiser -Meyer -Olkin measure of sampling adequacy 0.62, Bartlett ' s test of sphericity chi-squared (6) 413.07, P < 0.001), with all items loading clearly on one factor containing 42.76% of the variance.…”
Section: Methodsmentioning
confidence: 99%